2006
DOI: 10.1891/vv-v21i6a008
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Effects and Immune System Correlates of Rape

Abstract: The purpose of this study was to evaluate the feasibility of measuring stress hormones and immunity following rape. The long-term goal is to evaluate the predictive value of stress-immune-inflammatory responses to later health outcomes. Fifteen women reporting rape were compared with 16 control participants. Serum stress hormones, proinflammatory cytokines, acute phase proteins, functional assays, and lymphocyte subsets were measured in blood samples. Women reporting rape had higher cytotoxic cells, lower B ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These findings suggest that hormones may play a role in neuroendocrine responses to stress, and these observations may be especially important among women with abuse histories. Sexual violence victims also have poorer markers of physical health and immune function, including increased level of cytotoxic cells, lower B lymphocyte counts, higher proinflammatory biomarkers, and decreased lymphocyte proliferation compared with controls (Groer, Thomas, Evans, Helton, & Weldon, 2006).…”
Section: Biological Mechanisms Linking Sexual Violence To Adverse Con...mentioning
confidence: 99%
“…These findings suggest that hormones may play a role in neuroendocrine responses to stress, and these observations may be especially important among women with abuse histories. Sexual violence victims also have poorer markers of physical health and immune function, including increased level of cytotoxic cells, lower B lymphocyte counts, higher proinflammatory biomarkers, and decreased lymphocyte proliferation compared with controls (Groer, Thomas, Evans, Helton, & Weldon, 2006).…”
Section: Biological Mechanisms Linking Sexual Violence To Adverse Con...mentioning
confidence: 99%
“…Studies of CSA survivors have found hormonal disruption and dysregulartion of the HPA axis (DeBellis et al, 1994; King, Mandansky, King, Fletcher, & Brewer, 2001). In a study of ASA victims obtaining medical forensic exams, Groer, Thomas, Evans, Helton, and Weldon (2006) found that victims had significantly different immune/inflammatory functioning compared to nonassaulted controls. In the most comprehensive study on this topic to date, Woods et al (2005) developed a bio-psycho-immunologic theoretical model to explain how IPV affects women's physical health, which was empirically validated in a predominantly African American sample of 62 IPV victims (about half also experienced ASA in the relationship) and 39 nonabused women.…”
Section: Health Impact Of Multiple Forms Of Violence Against Womenmentioning
confidence: 99%
“…Inflammation was also found to be elevated in a study of 15 women who had been raped 24 to 72 hours after their assault, compared with 16 women who had not been sexually assaulted. Sexually assaulted women had higher ACTH, C-reactive protein, IL-6, IL-10, IFN-␥ than women in the nonassaulted group (Groe ¨r, Thomas, Evans, Helton, & Weldon, 2006).…”
Section: Inflammation In Trauma Survivorsmentioning
confidence: 99%